Evaluating socioeconomic inequalities in self-rated oral health and its contributing factors in Brazilian older adults. - Fabíola Bof de Andrade; José Leopoldo Ferreira Antunes (PLoS ONE)
Objectives This study aimed to evaluate socioeconomic inequalities in self-reported oral health among community-dwelling Brazilian older adults and evaluate the oral health factors contributing to the inequalities. Methods This was a cross-sectional study with data from the Brazilian National Health Survey conducted in 2019. The dependent variable is the self-report of oral health categorized as good or poor. Household per capita income in quintiles and schooling were used as socioeconomic variables. The explanatory covariates were age; gender; limitation in basic activities of daily living; number of teeth, use of dental prostheses; difficulty in eating; and recent dental visit. The Oaxaca-Blinder two-fold decomposition for binary outcomes was used to evaluate the factors contributing to the inequalities in self-reported oral health. Results Self-reported poor oral health was found among 35.8% of the dentate and 29.6% of the edentulous individuals. Poor self-reported oral health was more prevalent among older adults with low income and educational levels. Among dentate individuals, the difference in the proportion of poor self-reported oral health (the gap) between those with no schooling and those with some schooling was 12.8 percent points (p.p.), favoring the poor. The gap between dentate in the lowest and highest income groups was 14.8 p.p. favoring the poor. Among edentulous individuals, those with no schooling had a higher proportion of self-reported oral health (total gap 10.6 p.p.). Concerning income inequalities, the gap favored the poorer group and was 5.4 p.p. higher among individuals in the lowest income group. Conclusion The decomposition analyses suggested that oral health variables explained most of the education and income inequalities; difficulties in eating were the most contributing factor in both the dentate and edentulous groups. There was a relatively reduced contribution of recent dental visits to socioeconomic inequality.